Penyuluhan Pengelolaan Dan Pemanfaatan Tumbuhan Obat Serta Valuasi Ekonomi - Uly J Riwu Kaho; Yosep Lawa; Jhon Liem; Henny A Raga; Joritha Naisanu (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
The utilization of medicinal plants in Indonesia is still limited due to the lack of community knowledge on sustainable management and utilization, as well as low awareness of the economic valuation of medicinal plants. The purpose of this community service activity is to improve public understanding of the sustainable management and utilization of medicinal plants and provide insights into their economic valuation. The methods used in this service are counseling, training, and consultation with the community, using a participatory approach. The results obtained show an increase in participants' knowledge of medicinal plants, as well as a more positive attitude toward sustainable plant management. Furthermore, participants' skills in utilizing medicinal plants and calculating their economic valuation have also improved. In conclusion, the conducted counseling and training can enhance knowledge, skills, and public awareness, which in turn can support more sustainable and economically valuable medicinal plant management.